The Adaptation of Marketing Communication Strategies of MSMEs in Indonesia - Purwaningwulan, Melly Maulin; Wulandari, Tine Agustin; Anggaswari, Niluh Ayu (UPT Publikasi Ilmiah UNISBA, 2024)
Marketing communication strategies are an aspect that must adapt to changes or dynam- ics that affect business. This research aimed to determine the adaptation due to the dynamics of the policy regarding the TikTok Shop platform in Indonesia, which is considered to violate the regula- tion of Trade Minister of Indonesia Number 31 of 2023, which started to be effective on September 26, 2023. This research used a qualitative approach with the case study method; data was collected through observation and in-depth interviews. The informants consisted of MSMEs who use TikTok Shop to sell their products and marketing communications experts through purposive sampling as the informant selection technique. Research findings revealed that MSME owners understand and implement message source strategies that result in the ability to adapt to advances in digital marketing. MSME owners also understand the importance of selecting suitable media and clear creative strategies for conveying marketing messages. MSMEs affected by the dynamics of the Tik- Tok Shop policy in Indonesia should diversify their platforms and contents as the key to preventing possible obstacles. At the same time, awareness of change and the ability to adapt are the keys to success in the marketing communications strategy implemented by MSMEs.